Reflective journaling and metacognitive awareness: insights from a longitudinal study in higher education. Issue 2 (3rd March 2020) - Alt, Dorit; Raichel, Nirit
ABSTRACT: This mix-methods study sought to assess the effect of semi-structured and unstructured reflective journaling (RJ) on 97 undergraduate students' perceptions of their metacognitive awareness, classified into two main components: knowledge of cognition and regulation of cognition. Students' entries were analyzed based on a guiding scheme. The Metacognitive Awareness Inventory (MAI) was administered to the participants before (pretest) and after (posttest) a 13-week intervention. Multiple levels of reflective engagement were evident in the semi-structured RJ entries, whereas the unstructured entries were largely descriptive, and mainly related to students' short-term learning experiences. Semi-structured RJ was found effective in nurturing students' perceptions of their regulation of cognition. The present study adds to past work by showing how prompting questions might enable students to perceive themselves as self-regulated learners.